MEDICAL STUDENTS' PERCEPTIONS OF THEIR LEARNING ENVIRONMENT AT LAHORE MEDICAL AND DENTAL COLLEGE LAHORE - Zafar, Uzma; Daud, Seema; Shakoor, Qamar; Chaudhry, Abdul Majeed; Naser, Fahad; Mushtaq, Mehreen (Journal of Ayub Medical College Abbottabad, 2017)
Background: The present study was designed to assess medical students' perceptions of their learning environment at Lahore Medical and Dental College, Lahore. Methods: It was a cross-sectional descriptive study conducted at Lahore Medical and Dental College, Lahore. Five hundred and thirty-three students participated in this study. A questionnaire was used as a study tool, comprising of demographic information and the '˜Dundee Ready Education Environment Measure' (DREEM) inventory. Data was entered and analyzed using SPSS 21 package. A comparison of scores between different MBBS classes was done by using ANOVA. Comparison of scores between gender and high school education was done by using Mann-Whitney U tests. Results: Study population included 62% females and 32% males. About 58% of the participants were between 18-21 years and 42% were between 22-25 years of age. The mean total DREEM score was 120.27/200. The mean score of the domains: '˜Students' perceptions of learning' was 28.31/48, '˜Students' perceptions of teaching' was 26.92/44, '˜Students' academic self- perceptions' was 21.37/32, '˜Students' perceptions of atmosphere' was 27.72/48, and '˜Students' social self- perceptions' was 16.40/28. Total DREEM and its subclasses score was significantly higher in F. Sc. students than the students with A level/American board (p-value <0.001). When DREEM scores were analyzed according to gender, perceptions of both male and female were positive. Age had no significant bearing on the total DREEM scores or scores in its subclasses. Conclusion: Overall perceptions or experiences of the MBBS students of their learning environment at Lahore medical and Dental College, Lahore were more positive. Keywords: Learning environment; DREEM inventory; Students' perceptionswere more positive